Student Perceptions of WebCT in a Web-Supported Instructional Environment: Distance Education Technologies for the Classroom - James R. Lindner; Tim H. Murphy (Journal of Applied Communications, 2001)
Web-supported instruction is becoming more commonplace in today's colleges and universities (Lindner, Dooley, & Murphy, 2001). This paper explores student perceptions of the use of WebCT to support instructional objectives in a Web-supported environment. Data for the study were collected with a survey instrument using WebCT on-line testing tools. The results show WebCT contributed to students' ability to accomplish the course objectives. Students, however, continued to rely on print-based course materials and did not create student-centered on-line learning environments.